LIGHTWEIGHT METAL CONSTRUCTION REPRESENTED BY CROSS FARMS OF «PYATIGORSK»-2 TYPE - Alexander Surenovich Marutyan; Tamazy Leonidovich Kobaliya (Современная наука и инновации, 2022)
Authors give new technical solution for space cancelled bearing structures presented in a form of lightweight metal wares of buildings and constructs made from orthogonal systems of crossed farms of coverings modulus of «Pyatigorsk»-2 type